The Afflicted Spirits Here in the Prison: Religious Allegory in Measure For Measure (Philologia, 2021)
Religious allegory in Shakespeare’s Measure for Measure is explored and found to contain dualistic elements, primarily perceptible in the attitudes expressed towards sexuality and womanhood.
Keywords: Measure for Measure; religious allegory; dualism; woman